STUDI KANDUNGAN DAN SEBARAN NUTRIEN PADA PERAIRAN TELUK SWAGE, LOMBOK TIMUR - Donna Ayu Maylanda; Paryono Paryono; Ibadur Rahman (Jurnal Perikanan Unram, 2023)
Nutrition is a very important element in supporting the process of growth and development of marine organisms. The main source of natural phosphate and nitrate comes from the waters themselves through the process decomposition, the remains of dead organisms, wastedomestic, agricultural, animal husbandry, and feed residues which will be decomposed by bacteria so that they become nutrients. This research was conducted from September 2022 to July 2023 with 15 sampling points. The purpose of this study was to determine the nutrient content (ammonia, nitrate, and phosphate) and their distribution patterns in the waters of Swage Bay, East Lombok. The method of collecting data on samples and water quality directly and then the water samples were analyzed at the Marine Science Oceanography Laboratory, Mataram University. The water samples that have been described are then made a distribution pattern using the ArcGIS application with the IDW method. The content of nitrate concentrations in Swage Bay waters ranges from 0.172 – 1.624 mg/l, phosphate around 1.31 – 3.12 mg/l, and ammonia around 0.256 – 2.8 mg/l which exceeds the seawater quality standards set by Government Regulation No. 22 of 2021 and distribution pattern of nutrients nitrate, phosphate, and ammonia is quite varied. Factors that influence the distribution pattern are temperature, pH, DO, in the waters of Swage Bay, East Lombok.